SISTEM REPOSITORY BERITA DAN GAMBAR PADA HARIAN UMUM LAMPUNG POST - arkhiansyah, yuni (Jurnal Informatika, 2014)
The development of technology which is very fast force us to equalize with the performance of technology, therefore we are charged to be able to create an application which are useful and beneficial for people. It is proved with the increasing of the use of computer technology even gadgets. PT. Masa Kini Mandiri (Lampung Post) especially in the documentation section need an application to scan data of news and picture for simplifying the data management. Data of news and picture which are still placed in folder shared will be impact in losing or redudancy of the data, both news or picture. Repository or warehouse is needed for the saving or documentation interest of a manuscript or picture in PT. Masa Kini Mandiri (Lampung Post) especially in documentation section, therefore if those data are needed in certain time in the future, it can be used as it should.Therefore the repository system of news and picture is needed to accommodate the data, news or picture which are alrealy published by Lampung Post daily newspaper. While the manuscript and picture that are in formed of file can be saved by repository system, so it can simplify in searching those data, news or picture in the future.Keywords : Repository, Newspaper, Picture, File, Folder Shared